(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The search for cleaner, renewable energy sources is imperative due to the rising global energy demand and environmental issues related to fossil fuels. The possibility of biodiesel-ethanol blends as environmentally friendly substitutes for conventional diesel fuel is examined in this study. Air pollution and greenhouse gas emissions can be significantly reduced by using biodiesel, which is made from renewable resources like vegetable and animal fats. A bio-based alcohol called ethanol improves biodiesel by decreasing harmful emissions and increasing combustion efficiency. The disadvantages of each fuel are lessened by combining them, offering a workable and environmentally friendly diesel alternative. The study examines the body of research on biodiesel-ethanol blends’ stability, engine performance, and environmental effects. Important research shows how well these blends work to lower emissions and enhance engine performance. The stability of biodiesel-ethanol blends is also examined in the study, with a focus on the contribution of additives and surfactants to blend stability. CeO₂ nanoparticles and other advanced additions have demonstrated potential in enhancing combustion and lowering emissions. To sum up, mixes of biodiesel and ethanol present a practical and sustainable substitute for conventional diesel fuel. By lowering dangerous pollutants and enhancing engine performance, they have a major positive impact on the environment. Future research should focus on optimizing blend ratios, enhancing fuel stability, and exploring the use of advanced additives to maximize the potential of biodiesel-ethanol blends as a cleaner and more efficient fuel source.